RUANG PASCAKOLONIAL DALAM THE GOD OF SMALL THINGS KARYA ARUNDHATI ROY - Endang Suciati (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This paper discussed about the construction of space in The God of Small Things novel by Arundhati Royusing post-colonial space theory by Sara Upstone to find out the representation of the West and the East inside andand outside the domestic space including the post-colonial strategy used. It was because The God of Small Things seemedto talk about the condition of the dualistic post-colonial Indian society. Then, India itself is one of the dualistic postcolonial societies which means that it still holds its own traditions and runs the culture left by the colonial. Both colonialand Indian culture had their own rules with their borders that controlled people’s life but they were repressive to the society.The result of this analysis proved that in the context of domestic space and its surroundings, The God of Small Thingsshowed the representation of the West and the East that caused transgression and chaos. The chaos led to post-spaceoutside the home. Once, the novel showed that the post-space could also be done inside the home. Thus, the novel wasdeconstructing the construction, including the construction of post-colonial itself. It happened since the problem began indualistic conditions of post-colonial Indian.Keywords: colonial, post-colonial, chaos, post-space.